Pteris barklyae (Pteridaceae): A new combination and neotypication of Adiantum pallens for the fern flora of the Indian Ocean Islands - Zhang, Liang; Zhou, Xin-Mao; Gao, Xin-Fen; Zhang, Libing (Phytotaxa, 2014)
Pellaea barklyae, a fern endemic to the Seychelles, is transferred to the genus Pteris based on recent molecular studies. We also neotypified Adiantum pallens Swartz, a species endemic to Madagascar, Mauritius, and La Réunion.